2001
DOI: 10.1029/2001gc000163
|View full text |Cite
|
Sign up to set email alerts
|

Regional variations in volatile composition: Isotopic evidence for carbonate recycling in the Central American volcanic arc

Abstract: [1] Abstract: Gas data were collected from geothermal production fields, fumaroles, and hot springs in Central America in order to investigate the relation between volatile output and spatial distribution of volcanic systems. The 3 He/ 4 He ratios are 6.5 ± 0.7 R a throughout the region, indicating that helium is predominantly of mantle origin and is largely independent of variations in the characteristics of the arc. Lower ratios produced by radiogenic production within the Chortis Block are restricted to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
1
6

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 84 publications
5
62
1
6
Order By: Relevance
“…Fischer et al (2002) and Zimmer et al (2004) showed that the slab-derived contribution of N 2 to arc magmas in most of Costa Rica is <50% of the total, reflecting offscraping of N-rich hemipelagic sediments beneath Costa Rica. Along-arc variations in N 2 and CO 2 sources have also been observed by Snyder et al (2001) and Snyder et al (2003) in Central America and by Clor et al (2005) and Jaffe et al (2004) in the Sangihe arc, Indonesia and have been explained by crustal contributions, variations in subducted sediment composition, forearc devolatilization, and offscraping of oceanic sediments prior to subduction.…”
Section: Along-arc Variationsmentioning
confidence: 91%
See 1 more Smart Citation
“…Fischer et al (2002) and Zimmer et al (2004) showed that the slab-derived contribution of N 2 to arc magmas in most of Costa Rica is <50% of the total, reflecting offscraping of N-rich hemipelagic sediments beneath Costa Rica. Along-arc variations in N 2 and CO 2 sources have also been observed by Snyder et al (2001) and Snyder et al (2003) in Central America and by Clor et al (2005) and Jaffe et al (2004) in the Sangihe arc, Indonesia and have been explained by crustal contributions, variations in subducted sediment composition, forearc devolatilization, and offscraping of oceanic sediments prior to subduction.…”
Section: Along-arc Variationsmentioning
confidence: 91%
“…To date, gas discharges have been examined for helium, carbon, and nitrogen in Guatemala and Costa Rica Hilton et al, 2002;Shaw et al, 2003;Zimmer et al, 2004), and for helium and carbon in Nicaragua (Shaw et al, 2003) and along the entire length of the CAVA (Snyder et al, 2001). Snyder et al (2003) investigated the sources of nitrogen and methane in geothermal fluids along the Central American Arc.…”
Section: Introductionmentioning
confidence: 99%
“…It has been argued that geothermal well sam- ples are the most pristine samples since they originate from deep reservoirs (1^2 km depth) and are less prone to near-surface boiling and degassing [14]. To test this hypothesis we sampled at two di¡erent geothermal well sites on the £anks of active volcanoes^Momotombo and Miravalleŝ and compared the results to other sampling media (fumaroles in Momotombo's crater and bubbling hot spring gas on Miravalles' £ank).…”
Section: Integrity Of Resultsmentioning
confidence: 99%
“…A clear conclusion is that all water spring samples show evidence of crustal contamination : low 3 He/ 4 He values, low X values, extreme N 13 C values (313.4 to 31x) and generally high CO 2 / 3 He ratios. Such samples are thus considered highly susceptible to near-surface fractionating processes, which have modi¢ed C isotopes to extreme values (see [14] for further details).…”
Section: Integrity Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation